Pelatihan dan Pendampingan Pengelolaan Jurnal Berbasis Online Journal System pada Madrasah Aliyah NegeriÂ 1Â Kediri - Idris, Idris; Purnomo, Agus; Adi, Khofifatu Rohmah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2023)
The development of professional teachers, especially in the field of publications, requires a place that can accommodate their work. The initiation of creating a journal as a medium for teachers to actualize in it is a step forward that can be an inspiration for schools to continue to develop professionally and can be a reference for other schools. MAN I Kota Kediri is one of the public madrasah schools that is committed to developing themselves to the maximum and dares to seize opportunities related to the need to manage a new journal as a forum for the actualization of teachers. However, their lack of ability in journal management and expertise in scientific writing makes it difficult for them to perform the progressive program they have planned. This community service is to increase the capacity of journal managers at MAN 1 Kediri City. The method used in this activity is an in-service training program with training as well as mentoring for teachers as journal managers at MAN 1 Kediri City. The results of this study indicate that teachers can perform the registration process and submit scientific papers to the OJS that has been provided.